Corporate reporting quality, audit committee and quality of audit / Hashanah Ismail, Takiah Mohd. Iskandar and Mohd. Mohid Rahmat - Ismail, Hashanah; Mohd. Iskandar, Takiah (Accounting Research Institute (ARI) & Faculty of Accountancy, 2008)
The study investigates the effectiveness of audit committee in terms of the quality of reporting. Specifically, the study examines the relationship between quality of reporting of companies listed on the Bursa Malaysia and some elements of corporate governance namely the external audit and the audit committee. Characteristics of audit committee being examined include financial literacy, multiple directorships, independence of audit committee, and activeness of the committee. Good quality corporate reporting provides credible information of company performance to users for economic decisions. The quality of corporate reporting is determined based on the selection criteria for the National Annual Corporate Report Award 2002. The sample consists of fifty-four companies with good annual reports and fifty-four companies with poor annual reports. Using logistic regression, results show that only multiple directorships of audit committee members is significantly related to quality of reporting